RETRACTED: Comparing Long-Term Outcomes Following Radical and Partial Nephrectomy for cT1 Renal Cell Carcinoma in Young and Healthy Individuals. Issue 1 (1st February 2019) - Tan, Wei Shen; Berg, Sebastian; Cole, Alexander P; Krimphove, Marieke; Marchese, Maya; Lipsitz, Stuart R; Nabi, Junaid; Sammon, Jesse D; Choueiri, Toni K; Kibel, Adam S; Sun, Maxine; Chang, Steven; et al.
Abstract: Background: Despite randomized data demonstrating better overall survival favoring radical nephrectomy, partial nephrectomy continues to be the treatment of choice for low-stage renal cell carcinoma. Methods: We utilized the National Cancer Database to identify patients younger than 50 years diagnosed with low-stage renal cell carcinoma (cT1) treated with radical nephrectomy or partial nephrectomy (2004–2007). Inverse probability of treatment weighting adjustment was performed for all preoperative factors to account for confounding factors. Kaplan-Meier curves and Cox proportional hazards regression analyses were used to compare overall survival of patients in the two treatment arms. Sensitivity analysis was performed to explore the interaction of type of surgery and clinical stage on overall survival. Results: Among the 3009 patients (median age = 44 years [interquartile range (IQR) = 40–47 years]), 2454 patients (81.6%) were treated with radical nephrectomy and 555 patients (18.4%) with partial nephrectomy. The median follow-up was 108.6 months (IQR = 80.2–124.3 months) during which 297 patients (12.1%) in the radical nephrectomy arm and 58 patients (10.5%) in the partial nephrectomy arm died. Following inverse probability of treatment weighting adjustment, there was no difference in overall survival between patients treated with partial nephrectomy and radical nephrectomy (hazard ratio = 0.83, 95% confidence interval = 0.63 to 1.10, P  = .196). There were no statistically significant interactions between type of surgery and clinical stage on treatment outcome. Conclusions: There was no difference in long-term overall survival between radical and partial nephrectomy in young and healthy patients. This patient cohort may have sufficient renal reserve over their lifetime, and preserving nephrons by partial nephrectomy may be unnecessary.